2021
DOI: 10.21203/rs.3.rs-1055948/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between personality traits and self-care behaviors in patients with gastrointestinal cancer undergoing outpatient chemotherapy

Abstract: Purpose Practicing self-care behaviors is important for patients with gastrointestinal cancer undergoing outpatient chemotherapy. Knowledge of personality traits may be useful in providing individualized support that can improve self-care behaviors. Therefore, we assessed the association between personality traits and self-care behaviors in these patients. Methods This cross-sectional study was conducted among patients who received intravenous chemotherapy at a designated regional cancer hospital between Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Openness is partly related to self-care in T2DM [ 12 ] and specifically linked to high compliance with foot care and general self-care behaviors, but it yielded non-significant associations with glycemic control, diet, medication adherence, and physical activity. The inconsistent associations between openness and objective markers of glycemia or glycemic control are supported by previous work [ 29 , 75 ] but not for physical activity compliance [ 76 ]. This finding is very interesting as openness is a personality factor that is particularly related to adaptive coping [ 77 ] by reducing many of the negative short-term physical effects of environmental stressors.…”
Section: Reviewmentioning
confidence: 56%
See 1 more Smart Citation
“…Openness is partly related to self-care in T2DM [ 12 ] and specifically linked to high compliance with foot care and general self-care behaviors, but it yielded non-significant associations with glycemic control, diet, medication adherence, and physical activity. The inconsistent associations between openness and objective markers of glycemia or glycemic control are supported by previous work [ 29 , 75 ] but not for physical activity compliance [ 76 ]. This finding is very interesting as openness is a personality factor that is particularly related to adaptive coping [ 77 ] by reducing many of the negative short-term physical effects of environmental stressors.…”
Section: Reviewmentioning
confidence: 56%
“…It has been suggested that conscientiousness is a dutiful, achievement-oriented, orderly, and accepting of the rules trait [ 80 ], and therefore, people having this trait may show greater compliance with self-care activities and risk of diabetes [ 75 , 81 , 82 ]. Many other individual studies of people with chronic conditions other than diabetes consistently also found positive health benefits of being highly conscientious [ 76 , 83 - 85 ]. The observed results are also consistent with the conclusions of a systematic review that included 17 studies of adults with type 2 diabetes and found weak to moderate associations between weight management and personality traits such as neuroticism and conscientiousness [ 73 ].…”
Section: Reviewmentioning
confidence: 99%